THE RELATIVE RATES OF THE COMPANIES’ ABILITY TO PRODUCE BENEFITS - MIȘU, Nicoleta BĂRBUȚĂ (Annales Universitatis Apulensis Series Oeconomica, 2014)
The company’s ability to generate results from their production and sales can be determined by a series of rates comparing an indicator reflecting the results and an indicator reflecting the overall flow of the activity, generally measured by the turnover (sales) or total assets. Using the comparative method over a period of five years to five companies acting in the metallurgical sector in this paper has been analyzed the evolution of net operating margin rate, net profit rate, gross operating margin rate, rate of free cash-flow, return on total assets and return on equity. Based on these findings it was concluded that the variation of performance of the companies affects and influences funding arrangements considered by the companies’ managers.